Treatment of patients with immunodeficiency: Medication, gene therapy, and transplantation - Gesmar Rodrigues Silva Segundo; Antonio Condino-Neto (Elsevier, 2021)
Objectives: To provide an overview of drug treatment, transplantation, and gene therapy for patients with primary immunodeficiencies. Source of data: Non-systematic review of the literature in the English language carried out at PubMed. Synthesis of data: The treatment of patients with primary immunodeficiencies aims to control their disease, especially the treatment and prevention of infections through antibiotic prophylaxis and/or immunoglobulin replacement therapy. In several diseases, it is possible to use specific medications for the affected pathway with control of the condition, especially in autoimmune or autoinflammatory processes associated with inborn immunity errors. In some diseases, treatment can be curative through hematopoietic stem cell transplantation (HSCT); more recently, gene therapy has opened new horizons through new technologies. Conclusions: Immunoglobulin replacement therapy remains the main therapeutic tool. Precision medicine with specific drugs for altered immune pathways is already a reality for several immune defects. Advances in the management of HSCT and gene therapy have expanded the capacity for curative treatments in patients with primary immunodeficiencies.